Application Of Business Ethics and Good Corporate Governance To Company Financial Performance - Larasati Pingkan C.H; Sri Trisnaningsih (International Journal of Management Research and Economics, 2024)
This research aims to assess the relationship between the implementation of business ethics, Good Corporate Governance (GCG) practices, the role of the board of directors, and managerial accounting practices on company financial performance. Through a comprehensive literature analysis, evaluating empirical evidence from a number of relevant studies in this theme. The findings show that implementing strong business ethics can increase shareholder and creditor trust, which in turn has a positive impact on a company's financial performance. Furthermore, effective GCG practices, including transparency, accountability and independence of the board of directors, have been proven to have a significant impact on improving a company's financial performance. The role of the board of directors as a supervisor and strategic advisor also has an important role in ensuring compliance with ethical standards and GCG principles. On the other hand, thorough managerial accounting practices can help management make better decisions, which ultimately improves the company's financial performance. Therefore, uniting business ethics, GCG, the role of the board of directors, and managerial accounting is the main key in improving the company's overall financial performance. Keywords: Business Ethics, Good Corporate Governance, Board of Directors, Financial Performance.